Urgensi Pengesahan Undang-undang Perampasan Aset dalam Penegakan Hukum di Indonesia (Studi Putusan Nomor 1277 PK/PID.SUS/2024) - Ummu Faizah; I Gede Hartadi Kurniawan (LPPM Institut Pendidikan Nusantara Global, 2026)
Economic crimes, particularly corruption and money laundering, are systemic crimes that cause significant state losses and undermine public trust in legal institutions in Indonesia. The increasing complexity of these crimes, marked by sophisticated patterns of asset concealment and cross-jurisdictional transfers, often weakens the effectiveness of conventional criminal justice mechanisms. This condition raises fundamental legal concerns regarding the adequacy of the current criminal justice regime in ensuring optimal asset recovery. Against this backdrop, the ratification of the Asset Forfeiture Bill (RUU Perampasan Aset) emerges as an urgent legal necessity, as it introduces a non-conviction-based asset forfeiture (NCB) mechanism grounded in the in rem principle, allowing asset confiscation without waiting for a final criminal conviction.This study focuses on examining the judicial reasoning (rasio decidendi) in Supreme Court Decision Number 1277 PK/Pid.Sus/2024, which highlights that conventional criminal procedures face prolonged timelines, multi-layered judicial processes, and difficulties in tracing and recovering criminal proceeds, creating substantial obstacles to effective state loss recovery. The Court emphasized that reliance solely on criminal conviction as a precondition for asset forfeiture may undermine both the effectiveness of state loss recovery and the broader public interest in combating economic crimes. This consideration forms the legal basis for recognizing the necessity of a non-conviction-based forfeiture mechanism.Using a normative juridical method with statutory and conceptual approaches, supported by primary, secondary, and tertiary legal materials, this study finds that the decision illustrates the limitations of conventional criminal justice procedures while underscoring the urgency for legislative reform through the ratification of the Asset Forfeiture Law. The law would ensure more effective recovery of state losses, enhance legal certainty, and maintain a proportional balance between law enforcement objectives and human rights protection.